Sample processing effect on polymerase chain reaction used for identification of Campylobacter jejuni - Sabatková, Z; Pazlarová, J; Demnerová, K (Folia microbiologica, 2004)
Model samples of Campylobacter jejuni for polymerase chain reaction (PCR) were prepared by rapid and simple procedures consisting of centrifugation, proteinase K treatment, Chelex 100 treatment, and boiling lyses. A PCR based on specific amplification of the variable sequence of 16S rRNA gene was performed using Tth DNA polymerase and the PCR products were visualized by agarose gel electrophoresis. The assay allowed the detection of 10 CFU/mL C. jejuni in the physiological saline and 100 CFU/mL in the basic Park and Sanders broth.
Keywords: Sodium Chloride; Campylobacter coli; kultivační média; polymerázová řetězová reakce; Culture Media; Polymerase Chain Reaction; Animals; lidé; Campylobacter jejuni; Campylobacter; Food Microbiology; Humans; zvířata; chlorid sodný; potravinářská mikrobiologie